Collective Behaviors of Magnetic Active Matter: Recent Progress toward Reconfigurable, Adaptive, and Multifunctional Swarming Micro/Nanorobots - Jin, Dongdong; Zhang, Li (Accounts of chemical research, 2022)
Active matter refers to the nonequilibrium system composed of interacting units that continually dissipate energy at a single-unit level and transduce it into mechanical force or motion. Such systems are ubiquitous in nature and span most of the biological scales, ranging from cytoskeleton protein polymers at the molecular level to bacterial colonies at the cellular level to swarms of insects, flocks of birds, schools of fish, and even crowds of humans on the organismal scale. The consumption of energy within systems tends to induce the self-organization of active matter as well as the spontaneous emergence of dynamic, complex, and collective states with extraordinary properties, such as adaptability, reconfigurability, taxis, and so on. The research into active matter is expected to deepen the understanding of the underlying mechanisms of how the units in living systems interact with each other and regulate the flow of energy to improve the survival efficiency, which in turn can provide valuable insights into the engineering of artificial active systems with novel and practical collective functionalities.Because of the striking similarity in collective states, a colloidal system is an emerging approach to understanding the guiding principles of the coordinated activities in living systems. Thanks to the capabilities in batch fabrication, size control, and the modulation of interactions (e.g., dipole-dipole interactions, capillary forces, electrostatic interactions, and so on), various complex collective states have been reproduced and programmed in colloidal suspension through the elaborate design of compositions and unit-unit interactions. Among the developed colloidal systems, magnetic colloids energized by alternating magnetic fields demonstrate several unique advantages, including the high-degree-of-freedom and simple modulation of the magnetic field parameters as well as the excellent compatibility of the magnetic field with many application scenarios. Therefore, magnetic active matter not only constitutes a useful platform that leads to a discovery of fascinating emergent collective behaviors but also promises enormous potential in a variety of engineering fields.In this Account, we summarize and highlight the key efforts carried out by our group and others on the investigation of the collective behavior of magnetic active matter in the past 5 years. First, we elucidate the generation mechanisms of the emergent coordinated behaviors, which are classified according to the dominating interactions among agents, that is, the magnetic dipole-dipole interaction, hydrodynamic interaction, and weak interaction. Then we illustrate the construction of magnetic active matter with a higher level of collective effects and functionalities (e.g., reconfigurability, environmental adaptability, 3D swarming, cooperative multifunctionality, and so on) via the synergistic effects between magnetic fields and other fields. Next, potential applications of magnetic active matter are discussed, which mainly focus on the exploration in revolutionizing traditional biomedical fields. Finally, an outlook of future opportunities is presented to promote the development of magnetic active matter, which facilitates a better understanding of living counterparts and the further realization of practical applications.